National institutions should improve the information made available to patients about cervical smears. Issue 12 (December 2021) - Tudrej, Benoit V.; Dernoncourt, Marion; Rehman, Michaela B.; Mignot, Stéphanie; Boussageon, Rémy
Highlights: Information is truncated and pushes readers towards taking part in screening. Information is not in accordance with quality criteria of shared decision making. Documents written by institutions should be based on recognized scientific sources. Abstract: Objective: To assess the quality of the content of leaflets tools and websites of national institutions in United Kingdom and France informing patients about cervical smears. Methods: We collected and analyzed the data and information on these two websites and leaflets made for patients. We screened those tools with the UP TO DATE SCIENTIFIC EVIDENCE IPDAS grid. Results: None of the tools specify the level of evidence of the studies on which cervix cancer screening is based. The risk of complication due to cancer is poor. The effectiveness of screening in absolute value is not available. The risks and side-effects due to cervical smears are specified without the frequency. Conclusion: Information is truncated and pushes readers towards taking part in screening. This is not in accordance with the quality criteria of shared decision making. Practice implications: Patients should take part in the creation of decision making tools, so that the information is the most suited to their representations and understanding. This is why the documents made available by institutions should be based on recognized scientific sources. Responsible of health programs should be independent and separated from those responsible of information tool creation.